Pengaruh Brand Image, Social Media, Dan Daya Tarik Wisata Terhadap Minat Berkunjung Pada Objek Wisata Kampung Heritage Kayutangan Kota Malang - Rahmat Rahmat; Jeni Susyanti; Ratna Tri Hardaningtyas (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The purpose of this research is to find out and analyze brand image, social media, and tourist attraction that influence simultaneously and partially on interest in visiting the tourism object of the Kayutangan Heritage Village, Malang City. In measuring this variable, the dependent variable is interest in visiting while the independent variables are brand image, social media, and tourist attraction. In this research, the type of research used is quantitative research with a descriptive approach. The quantitative research method is a type of research whose specifications are systematic, planned and clearly structured from the start to the creation of the research design. The method used in managing data uses multiple linear regression analysis through the SPSS program. The data used are primary data as well as secondary data obtained using interview techniques, questionnaires, direct and indirect observation. The sample in this study is unknown so in this study using the maholtra formula with details of 14 indicators x 5 = 70. From data processing, it was found that simultaneously and partially the variables Brand image, Social media, and Tourist attraction affect Interest in visiting objects Kayutangan Heritage Village Tour, Malang City. Keywords: Brand image, Social media, Tourist attraction, Interest in visiting